2016
DOI: 10.1061/(asce)mt.1943-5533.0001630
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Plasterboards: Experimental Tests and Statistical Analysis

Abstract: Plasterboard components are widely used in current buildings worldwide. Despite their extensive use, the lack of a comprehensive test campaign on plasterboards in the current literature is denoted. An extensive test campaign, consisting of 302 tests, on plasterboards is performed both in tension and compression. A set of five plasterboard typologies is selected. The tests are performed in two different load directions, i.e. parallel or transversal to the direction of production. Tensile strength of boards is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Gypsum plasterboards were composed of a plaster core encased in and firmly bonded to outer paper liners. Due to its fabrication method, the lining and also the board as a whole showed significant anisotropic properties [17][18][19][20]. Therefore, the mechanical properties of plasterboard sheets were determined in parallel and perpendicular to the sheet production direction, applying standard EN 520 [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gypsum plasterboards were composed of a plaster core encased in and firmly bonded to outer paper liners. Due to its fabrication method, the lining and also the board as a whole showed significant anisotropic properties [17][18][19][20]. Therefore, the mechanical properties of plasterboard sheets were determined in parallel and perpendicular to the sheet production direction, applying standard EN 520 [21].…”
Section: Methodsmentioning
confidence: 99%
“…This experiment showed that product merely discarded in the environment could be also recycled. The influence of humidity on the properties of concrete was investigated by using contact and non-contact methods and was reported in [17], but, so far, no similar research in relation to plasterboards was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Gypsum plasterboard has relatively low compressive and tensile strengths which can result in early onset of damage [57,71]. The corners of the gypsum plasterboards crushed, creating wrinkles Table 7: Parameters for the tested specimen.…”
Section: Propagation Of Observed Damage and Hysteretic Responsementioning
confidence: 99%
“…The LSF is the only material to be considered for the loadbearing capacity of the wall. All other materials, that may contribute to the strength and collapse mode of the structure (Petrone, Magliulo, & Manfredi, 2016), will not be considered for the calculation of the loadbearing capacity. An incremental and iterative solution method was applied to determine the loadbearing capacity.…”
Section: Numerical Analysismentioning
confidence: 99%